The Role of Learning Evaluation in Improving Teachers’ Islamic Religious Education Competency - Rifki Abadullah; Wendi Saepul Mikdar; Bambang Samsul Arifin; Mulyawan Syafwandy Nugraha (CV. Creative Tugu Pena, 2024)
This research aims to improve the quality of competency of Islamic religious education teachers through the important role of evaluation in the learning process. The method used in this research is library research by critically and in-depth reviewing library materials that are relevant to paper materials such as books and journals that are suitable as references. This data collection uses the source search method and constructs it from various sources, for example books, journals and research that has been carried out. Based on the research process, evaluation is very important in efforts to improve the quality of teacher competence, so this process must be carried out regularly in order to create quality educators. This can be done through several aspects, namely; transparency and openness, assessment instruments, evaluator training, follow-up and support.